Efektivitas Pemberantasan Pungutan Liar dalam Pelayanan Publik di Desa Pangsan Kecamatan Petang Kabupaten Badung - I Putu Putra Ariasa; Ida Ayu Putu Widiati; Luh Putu Suryani (Jurnal Interpretasi Hukum, 2020)
Illegal levies are a form of crime that is very familiar to the public. Basically, illegal levy and corruption are the same acts where the two acts use power for the purpose of enriching themselves by violating the law. Based on the background of this problem, this research was conducted with the aim of describing the implementation of public services at Pangsan Village office, Petang District and the effectiveness of illegal levies eradication on public services at Pangsan Village office, Petang District. This study employed an empirical legal research method. The results of this study indicated that the implementation of public services at Pangsan Village office, Petang District has met technical indicators in accordance with work procedures. In Pangsan Village, the standard procedures also have the function of forming an orderly, systematic, and accountable work system and workflow. the effectiveness of illegal levies eradication on public services at the Pangsan Village office, Petang District has been very effective through the efforts made to prevent illegal levies in administrative services.